2022
DOI: 10.1186/s13018-022-02918-8
|View full text |Cite
|
Sign up to set email alerts
|

Why and how to use the body's own stem cells for regeneration in musculoskeletal disorders: a primer

Abstract: Background Recently, the management of musculoskeletal disorders with the patients' own stem cells, isolated from the walls of small blood vessels, which can be found in great numbers in the adipose tissue, has received considerable attention. On the other hand, there are still misconceptions about these adipose-derived regenerative cells (ADRCs) that contain vascular-associated pluripotent stem cells (vaPS cells) in regenerative medicine. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…The isolation of stem cells from suitable tissue (such as adipose tissue) and their application to other injured tissue and organs can be interpreted as the most gentle and natural approach to help the body in self-repair by increasing the number of stem cells at a location where they are exhausted but most needed. From these considerations, it also becomes clear that stem cell therapy is not only directed to a specific organ, tissue, or disease, but it will take the function of replacing and repairing tissue and organs that suffer from a lack of repair, renewal, and rejuvenation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation of stem cells from suitable tissue (such as adipose tissue) and their application to other injured tissue and organs can be interpreted as the most gentle and natural approach to help the body in self-repair by increasing the number of stem cells at a location where they are exhausted but most needed. From these considerations, it also becomes clear that stem cell therapy is not only directed to a specific organ, tissue, or disease, but it will take the function of replacing and repairing tissue and organs that suffer from a lack of repair, renewal, and rejuvenation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In degenerative diseases of joints, damage to functional tissue induces an inflammatory process, resulting in pain. It has been shown that painful chronic inflammatory disorders of the musculoskeletal system can successfully be treated by stem cell injection [ 16 ]. Stem cells, in general, often called MSCs in an inflammatory environment, can influence the immune response by altering cytokine secretion from macrophages, dendritic cells, and T-cell subsets, resulting in a shift from a pro-inflammatory to an anti-inflammatory environment.…”
Section: Introductionmentioning
confidence: 99%
“…In degenerative diseases of joints, damage to functional tissue induces an inflammatory process, resulting in pain. It has been shown that painful chronic inflammatory disorders of the musculoskeletal system can successfully be treated by stem cell injection [19]. Stem cells, in general, often called MSCs in an inflammatory environment, can influence the immune response by altering cytokine secretion from macrophages, dendritic and T-cell subsets, resulting in a shift from a pro-inflammatory to an anti-inflammatory environment.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, extensive investigations have been performed on MSC therapy in bone repair alone or in combination with other remedies [ 3 , 4 ]. Interestingly, there are reports showing that adipose-derived mesenchymal stem cells (ASCs) are an appropriate source for the treatment of skeletal disorders such as musculoskeletal diseases and shoulder pains [ 5 7 ]. Systemic and local administration of allogeneic bone marrow-derived mesenchymal stem cells (BM-MSCs) in rat femoral bone fracture led to an elevation in the callus formation and osteoblast differentiation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%